IL-33-primed human mast cells drive IL-9 production by CD4+ effector T cells in an OX40L-dependent manner - Battut, Louise; Leveque, Edouard; Valitutti, Salvatore; Cenac, Nicolas; Dietrich, Gilles; Espinosa, Eric (Frontiers in Immunology, 2024)
Interleukin-33 (IL-33) is an alarmin released by epithelial cells in response to tissue damage. It activates resident immune sentinel cells, which then produce signals commonly associated with type 2 immune responses, particularly affecting infiltrating antigen-specific T cells. Given that mast cells (MCs) are a primary target of IL-33 and can shape T helper (Th) cell responses, we investigated the effect of IL-33 priming on the ability of MCs to influence Th cell cytokine production. To examine the Th cell/MC interaction, we developed human primary MC/memory CD4+ T-cell coculture systems involving both cognate and non-cognate interactions. Our results demonstrated that IL-33-primed MCs, whether as bystander cells cocultured with activated effector T cells or functioning as antigen-presenting cells, promoted IL-9 and increased IL-13 production in Th cells via an OX40L-dependent mechanism. This indicates that MCs sense IL-33-associated danger, prompting them to direct Th cells to produce the key type 2 effector cytokines IL-9 and IL-13.